The Influence of Different Light Wavelengths of Anthropogenic Light at Night on Nestling Development and the Timing of Post-fledge Movements in a Migratory Songbird - Bani Assadi, Saeedeh; Fraser, Kevin C. (Frontiers in Ecology and Evolution, 2021)
Abstract Many different aspects of an animal’s lifecycle such as its behaviour, patterns of hormone activity, and internal clock time, can be affected by anthropogenic light at night (ALAN). Exposing an organism to ALAN during its early life could also have an impact on its development. Since photoperiod can trigger or schedule the migration timing of long-distance migratory birds, there is great potential for anthropogenic light to interact with photoperiod to affect timing. However, very little has been investigated regarding the impacts of ALAN on post-hatching development and migration timing. We investigated the impact of ALAN during nestling development in a long-distance migratory songbird to determine the potential impact on the timing of post-breeding movements in the wild. We experimentally manipulated the light by using programmable lighting, in the nest boxes of free-living nestlings of purple martin (Progne subis) in Manitoba, Canada. We exposed two groups of developing nestlings, from hatch to fledge date, to green or white LED lights (5 lux) during the night. We also included a control group that experienced natural, ambient light at night. We found that some adults abandoned their nests shortly after starting the experiment (4 of 15 nests in the white light treatment). For the nests that remained active, nestlings exposed to the white light treatment had higher weights (at day 20 or 22), later fledge dates (1.54 ± 0.37, 95% CI 0.80 to 2.28), and later colony departure date (2.84 ± 1.00, 95% CI 0.88 to 4.81), than young of the control group. Moreover, nestlings of both white and green light groups had longer nesting duration than nestlings of the control group. This study demonstrates the impact of ALAN on the development of post-breeding movement timing in nestlings of wild migratory birds. However, our results also indicate that green light may have less of an impact as compared to white light. Keywords: Light pollution, Artificial Light At Night, phenotypic plasticity, post-breeding movements timing, ontogenetic effect